2020
DOI: 10.1021/acs.jpclett.9b03484
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Four-Fold Boron–Metal Bonds in RhB(BO) and RhB

Abstract: The maximum bond order between two main-group atoms was known to be three. However, it has been suggested recently that there is quadruple bonding in C 2 and analogous eight-valence electron species. While the quadruple bond in C 2 has aroused some debates, an interesting question is: are main-group elements capable of forming quadruple bonds? Here we use photoelectron spectroscopy and computational chemistry to probe the electronic structure and chemical bonding in RhB 2 O − and RhB − and show that the boron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
84
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 36 publications
11
84
2
1
Order By: Relevance
“…Above 5.5 eV, the signal-to-noise ratios are poor, and no definite spectral transitions can be identified. It should be pointed out that the overall 193 nm spectral pattern of IrB 2 O À shows some similarities to that of the recently reported RhB 2 O À , [10] suggesting they may have similar structures.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Above 5.5 eV, the signal-to-noise ratios are poor, and no definite spectral transitions can be identified. It should be pointed out that the overall 193 nm spectral pattern of IrB 2 O À shows some similarities to that of the recently reported RhB 2 O À , [10] suggesting they may have similar structures.…”
supporting
confidence: 69%
“…[6] The structure and bonding of IrB 2 O À are similar to RhB 2 O À , which has a Rh B quadruple-bond character. [10] The difference of bonding in the two isoelectronic systems lies in the BÀMÀB bond angles and the 3c-2e BÀMÀB bond. The BÀRhÀB bond angle is 99.88 and therefore larger than the BÀIrÀB bond angle of 91.58.…”
Section: Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Chemie Zuschriften global minimum of RhB 2 O À reported recently. [10] The linear isomer for IrB 2 O À ( 1 S + ) was found to be 0.58 eV higher in energy ( Figure S1 a). However, we found that the global minimum of ReB 2 O À is linear with a short ReÀB bond and a BO À unit bonded to the B atom.…”
Section: Methodsmentioning
confidence: 99%
“…This led to the discovery of the first Rh B quadruple bond in a diatomic molecule involving boron. [10,11] In the meantime, a combined infrared and theoretical study on BFe(CO) 3…”
mentioning
confidence: 99%